Locus of Control and Psychological Capital: The Key to Success for Thrifting Entrepreneurs - Bangsa, Galang Sukma; Wibowo, Doddy Hendro (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Psychological capital is one of the important personal resources for entrepreneurs, especially when they are in a less conducive environment. In addition to psychological capital, locus of control is also an important element in influencing an entrepreneur in running his business. This study aims to determine the relationship between locus of control and psychological capital in thrifting entrepreneurs. This study used snowball sampling technique and involved 110 thrifting entrepreneurs. The data collection method used the IPC-Locus of Control Scale and Psychological Capital Questionnaire-24 (PCQ-24). Based on the results of data analysis using Spearman rank correlation coefficient, the correlation coefficient between internal locus of control and psychological capital is 0.235 with a p value of 0.007 (p < 0.05) and the correlation coefficient between external locus of control and psychological capital is -0.259 with a p value of 0.003 (p < 0.05). Thus, thrifting entrepreneurs with high internal locus of control tend to have high psychological capital. The effort that thrifting entrepreneurs can make to increase psychological capital is to believe that everything that happens to their business is dominated by internal factors such as their ability to manage their business plays an important role in the progress of their business.Psychological capital merupakan salah satu sumber daya pribadi yang penting bagi wirausahawan, terutama saat berada dalam lingkungan yang kurang kondusif. Selain psychological capital, locus of control juga merupakan elemen yang penting dalam mempengaruhi seorang wirausahawan dalam menjalankan usahanya. Penelitian ini bertujuan untuk mengetahui hubungan antara locus of control dengan psychological capital pada wirausahawan thrifting. Penelitian ini menggunakan teknik snowball sampling dan melibatkan wirausahawan thrifting sejumlah 110 orang. Metode pengumpulan data menggunakan Skala IPC-Locus of Control dan Psychological Capital Questionnaire-24 (PCQ-24). Berdasarkan hasil analisis data menggunakan Spearman rank correlation coefficient, didapatkan koefisien korelasi antara locus of control internal dengan psychological capital sebesar 0,235 dengan nilai p sebesar 0,007 (p < 0,05) dan koefisien korelasi antara locus of control eksternal dengan psychological capital sebesar -0,259 dengan nilai p sebesar 0,003 (p < 0,05). Dengan demikian, wirausahawan thrifting dengan locus of control internal tinggi cenderung memiliki psychological capital yang tinggi. Upaya yang dapat dilakukan wirausahawan thrifting untuk meningkatkan psychological capital adalah dengan meyakini bahwa segala sesuatu yang terjadi pada usahanya didominasi oleh faktor internal seperti kemampuannya dalam mengelola usaha berperan penting dalam kemajuan usahanya.